(untitled) (Journal of Bangladesh Academy of Sciences, 2014)
In this paper, intuitionistic fuzzy T0 spaces were studied. The authors investigated some relations among them and also investigated the relationship between intuitionistic fuzzy topological spaces and intuitionistic topological spaces DOI: http://dx.doi.org/10.3329/jbas.v38i2.21344 Journal of Bangladesh Academy of Sciences, Vol. 38, No. 2, 197-207, 2014